Metaphor in Hamka’s Biography Novel: A Semiotic Study - Wini Tarmini; Imam Safi'i; Deyana Wanda Aulia (Randwick International of Education and Linguistics Science Journal, 2022)
This study aimed to describe language symbols having wider meaning, metaphoric meaning, and socio-cultural background of HAMKA’s biography novel. The method used was descriptive qualitative. Findings of this study showed that the language symbols consisted of: ikon, indek, and simbol; aspect of meaning consisted of conceptual and metaphoric meaning. Metaphoric meaning was reflected in rethorical utterance. Out of 18 rethotical utterances, there were 12 rhetorical utterances which contained klimaks, Antithesis, Apostrof, Seruan, Hiperbola, Litotes, Simile, Metonimi, Ironi, Paradoks, Personifikasi, and Pertanyaan Retoris. Based on analysis, metaphoric and rhetorical meaning showed socio-cultural background of society which tended to reveal personal interpretation and subjective feeling indirectly.